A fundamental-period-preserving seismic retrofit methodology for low-rise buildings with supplemental inerters. (1st September 2022) - Lu, Wei-Ting; Phillips, Brian M.
Highlights: An innovative seismic retrofit methodology combining stiffness retrofit with inerters is proposed for low-rise buildings. The approach resolves shortcomings of traditional stiffness retrofit techniques. The approach reduces the required stiffening and foundation strengthening. Both displacement and acceleration responses can be reduced. The practicality of the retrofit approach is addressed. Abstract: Stiffness retrofit is a very effective technique to increase the seismic capacity of low-rise buildings. However, the shift of the fundamental period might lead to potential adverse effects when considering the spectral content of the ground motions. To address this issue, this paper proposed a fundamental-period-preserving (FPP) retrofit methodology. By augmenting traditional stiffness retrofit techniques with inerters, the fundamental period can be preserved. In addition, the normalized seismic input force and higher mode effects can be reduced. Different retrofit examples were evaluated through a series of nonlinear static and nonlinear dynamic analyses. Different performance objectives, including roof drift, story drift, story acceleration, base shear, and the force generated by inerters were used to demonstrate the effectiveness and the applicability of FPP approach in structure retrofit. The results showed that the FPP approach is an attractive alternative to the seismic retrofit of low-rise buildings.